2013
DOI: 10.1002/piq.21149
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Mentoring

Abstract: Mentoring involves the use of an experienced individual to teach and train someone with less knowledge in a given area. Through individualized attention the mentor/teacher transfers needed information, feedback, and encouragement to the protegé/learner. The success of such a program depends heavily on the investment of effort by the mentor. Although benefits for the protegé are typically easily discerned and have been well documented in the past, the factors affecting motivation for the mentor have been less w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…One such way is by offering support and assistance to coworkers. The mentoring literature has suggested that employees believe that providing assistance to others can be beneficial for one's image (Allen, Poteet, & Burroughs, 1997;Newby & Heide, 1992;Noe, Greenberger, & Wang, 2002), and the impression management literature has supported this assertion. For example, Grant and Mayer (2009) showed that image-building motives are strongly correlated with prosocialhelping motives (r ¼ .49), and that employees who desired to help others were more likely to do so when they were also determined to improve their image.…”
Section: Generous Actsmentioning
confidence: 99%
“…One such way is by offering support and assistance to coworkers. The mentoring literature has suggested that employees believe that providing assistance to others can be beneficial for one's image (Allen, Poteet, & Burroughs, 1997;Newby & Heide, 1992;Noe, Greenberger, & Wang, 2002), and the impression management literature has supported this assertion. For example, Grant and Mayer (2009) showed that image-building motives are strongly correlated with prosocialhelping motives (r ¼ .49), and that employees who desired to help others were more likely to do so when they were also determined to improve their image.…”
Section: Generous Actsmentioning
confidence: 99%
“…There are many industrial approaches to supporting and advancing staff, whether through training, appraisal or coaching. Mentoring has been identified as a method which can boost morale, increase job satisfaction (Fagenson, 1992: Newby and Heide, 1992) and ultimately affect the bottom line. However, there are many challenges with mentoring staff in the tourism industry.…”
Section: Mentoring Within the Tourism Sectormentioning
confidence: 99%
“…At the less structured end of the spectrum, organizations may haphazardly match mentors and protégés on some criteria (e.g., proximity, gender, job function), plan an initial social gathering and hope for the best—or that some learning transpires over the ensuing months. More structured programs may involve carefully matching pairs, conducting training for both mentors and protégés, conducting follow-up checks to ensure the relationship is on track, and assisting pairs in development of learning goals (Gaskill, 1993; Kram & Bragar, 1992; Newby & Heide, 1992; Tyler, 1998). In a review of best practices for formal programs, Kram and Bragar (1992) noted that mentoring will be most successful when tied to the business goals of the organization.…”
Section: Mentoringmentioning
confidence: 99%